Optimal Transmission Network for a Green Hydrogen Project in Magallanes, Chile - Chavez-Orostica, H (Institute of Electrical and Electronics Engineers Inc., 2024)
This paper addresses the optimal planning of the electrical grid in the Magallanes Region, focusing on integrating wind farms and distributing energy to industrial facilities for green hydrogen production. A mathematical optimization model based on linear power flow and genetic algorithms was developed to establish the transmission network s topology. Considering geographical, environmental, and power data, the study offers a robust methodology for sustainable planning of electrical systems in remote areas with renewable resources. © 2024 IEEE.